Reflex sympathetic dystrophy associated with squamous cell carcinoma of the lung. Issue 4 (April 1989) - Prowse, M; Higgs, C M; Forrester-Wood, C; McHugh, N
Abstract : Reflex sympathetic dystrophy was the presenting feature in an otherwise occult case of non-metastatic squamous cell carcinoma of the lung which improved on surgical removal of the primary tumour. Reflex sympathetic dystrophy, therefore, should be considered an occasional manifestation of a paraneoplastic syndrome warranting a thorough search for underlying malignancy.